Empirical model the research of historical generation throughthe products of photo and movie art - Fetisova, Catherine (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
This article focuses on building empirical models study the concept of a historical figure in the light of product photography and film art. In this respect we define the context of historical understanding of the concept generation and historical identity, product review art as a reflection of a reality captured. The article presents a model for building empirical research.
Keywords: the historic generation; historical figure; a reflection of reality; product photography and film art